2007
DOI: 10.1038/sj.gene.6364417
|View full text |Cite
|
Sign up to set email alerts
|

Positive replication and linkage disequilibrium mapping of the chromosome 21q22.1 malaria susceptibility locus

Abstract: Four cytokine receptor genes are located on Chr21q22.11, encoding the a and b subunits of the interferon-a receptor (IFNAR1 and IFNAR2), the b subunit of the interleukin 10 receptor (IL10RB) and the second subunit of the interferon-g receptor (IFNGR2). We previously reported that two variants in IFNAR1 were associated with susceptibility to malaria in Gambians. We now present an extensive fine-scale mapping of the associated region utilizing 45 additional genetic markers obtained from public databases and by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…In Gambian children, two SNPs, which were identified in the IFNAR1 gene in intron 3 and exon 4, were associated with severe malaria and CM (13). However, the study of Gambian, Kenyan, and Vietnamese populations (14) highlighted positive associations in the 59 region of the IFNAR1 locus. This was also found as a region of strong association in our study, suggesting that the 59 region of the IFNAR1 gene known to control transcriptional activity (35) represents a malaria-susceptibility factor throughout diverse populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Gambian children, two SNPs, which were identified in the IFNAR1 gene in intron 3 and exon 4, were associated with severe malaria and CM (13). However, the study of Gambian, Kenyan, and Vietnamese populations (14) highlighted positive associations in the 59 region of the IFNAR1 locus. This was also found as a region of strong association in our study, suggesting that the 59 region of the IFNAR1 gene known to control transcriptional activity (35) represents a malaria-susceptibility factor throughout diverse populations.…”
Section: Discussionmentioning
confidence: 99%
“…The IFNAR1 gene has been associated with severe forms of malaria (13,14). In this study, we used a cohort of Angolan children to identify IFNAR1 genetic variants that specifically modify the risk for progressing from uncomplicated forms of malaria to CM syndrome.…”
Section: Ifnar1 Variants Are Associated With Protection Against Clinimentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies of malaria-infected patients have found an association between mutations within IFN-␣ receptor (IFN-␣R) and severe disease susceptibility, suggesting that the type I IFN pathway may play a role in severe disease (3,17). IFN-␣ has been identified in a subset of malaria-infected patient sera (25,29).…”
Section: Discussionmentioning
confidence: 99%
“…A promoter polymorphism each of IFNA2 and IFNA8 has recently been shown to be associated with reduced IFNa production and increased susceptibility to severe malarial anaemia and mortality in Kenyan populations (Kempaiah et al, 2012). Association of IFNAR1 variants with protection against severe and cerebral malaria in African and South East Asian populations has also been reported (Aucan et al, 2003;Ball et al, 2013;Khor et al, 2007).…”
Section: Introductionmentioning
confidence: 94%